Cyberreligion: the role of artificial intelligence as a communication medium for religious education learning in the digital era - Andriani, Astri Dwi; Sudirman, Sudirman (TARBAWY: Indonesian Journal of Islamic Education, 2023)
This research aims to obtain descriptive knowledge regarding the presence of cyberreligion, which includes discussing the role of artificial intelligence as a learning medium for Islamic religious education in the digital era. This phenomenon is studied through qualitative research using the literature review or literature review method. Data collection methods include documentation techniques by searching for data from magazines, books, online news media, etc. The research results show that currently artificial intelligence has become a learning communication medium for Islamic subjects through various methods, including: 1) matching and searching for N-gram based words; 2) search for the Al-Quran index; 3) increasing the accuracy of answers in the Al-Quran translation question and answer system; 4) application for memorizing verses of the Koran; 5) Islamic portal; 6) Islamic social media; 7) file sharing; and 8) Islamic chat in cyberspace. The development of artificial intelligence must also not be separated from Islamic ethics.